The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1152/physrev.00006.2022
|View full text |Cite
|
Sign up to set email alerts
|

Complex physiology and clinical implications of time-restricted eating

Abstract: Time-restricted eating (TRE) is a dietary intervention that limits food consumption to a specific time window each day. The effect of TRE on body weight and physiological functions has been extensively studied in rodent models, which have shown considerable therapeutic effects of TRE and important interactions among time of eating, circadian biology and metabolic homeostasis. In contrast, it is difficult to make firm conclusions regarding the effect of TRE in people because of the heterogeneity in results, TRE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 389 publications
0
25
0
Order By: Relevance
“…Time-restricted eating (TRE): This approach is the only IF subtype that does not place a strong emphasis on caloric restriction. 1 The fast's length and the eating window's timing are significant factors that could impact physiological outcomes. 15,16 Although there is heterogeneity between different TRE practices, with eating windows varying from as little as four hours 17,18 to as long as 12 hours 19,20 per day, the window duration most frequently reported in clinical studies is eight hours.…”
Section: Types Of Intermittent Fastingmentioning
confidence: 99%
“…Time-restricted eating (TRE): This approach is the only IF subtype that does not place a strong emphasis on caloric restriction. 1 The fast's length and the eating window's timing are significant factors that could impact physiological outcomes. 15,16 Although there is heterogeneity between different TRE practices, with eating windows varying from as little as four hours 17,18 to as long as 12 hours 19,20 per day, the window duration most frequently reported in clinical studies is eight hours.…”
Section: Types Of Intermittent Fastingmentioning
confidence: 99%
“…Circadian rhythmicity has been observed in numerous physiologic functions including sleep-wake cycles, metabolism, and hormonal release. This rhythmicity is governed by a core set of genes, known as "clock genes," that act as transcriptional and translational activators and repressors [24,25].…”
Section: T a B L E 1 Summary Of Relevant Trf Studies In Rodentsmentioning
confidence: 99%
“…Fasting elicits a series of adaptive changes, such as reducing basal metabolic rates, inducing lipolysis and ketogenesis, modulating hormone concentrations, and decreasing oxidative stress and inflammation. [32][33][34][35] Correspondingly, numerous preclinical and clinical studies have demonstrated the benefits of fasting in preventing and/or resisting multiple diseases. [36][37][38][39] Here, we aim to provide a timely and comprehensive view of the multifaceted role of fasting in both physiological and pathological states.…”
Section: Introductionmentioning
confidence: 99%